Ethics and Elegance: How Sustainability Shapes Luxury and Fast Fashion Perception in the UAE - Abdelmaksoud, Radwa (2025)
A Master of Business Administration (MBA) thesis by Radwa Abdelmaksoud entitled, “Ethics and Elegance: How Sustainability Shapes Luxury and Fast Fashion Perception in the UAE”, submitted in May 2025. Thesis advisor is Dr. Rania Semaan. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form).